Evaluasi Program Pendidikan Ahklak di SMAN 5 Payakumbuh - Fatma Sari; Supratman Zakir; Darul Ilmi; Susanda Febriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to evaluate the effectiveness of the moral education program at SMAN 5 Payakumbuh, focusing on four main aspects: policy support, resources, implementation, and student morals. The underlying problem of this research is the importance of moral education in shaping students' character in the educational environment. The research methodology uses the CIPP (Context, Input, Process, Product) evaluation model that integrates qualitative and quantitative approaches. The context evaluation highlights school policy support for the program, the input evaluation evaluates the availability of human and material resources, the process evaluation audits the implementation of the program, and the product evaluation evaluates its impact on changes in student attitudes and behavior. The results show that the moral education program at SMAN 5 Payakumbuh has had a significant positive impact, with noticeable improvements in discipline, responsibility, as well as student participation in positive activities. The implications of this study provide a strong basis for the development and improvement of moral education programs in schools, as well as making an important contribution to understanding the effectiveness of character education strategies in SMAN 5 Payakumbuh.